(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article gives a brief overview of the rise of AI, the services it offers and the fears it arouses, and then uses concrete examples to focus on the possibilities offered by different types of AI, depending on the tasks to be carried out, to enrich and improve the teaching of French as a foreign language with a view to efficiency, thanks in particular to approaches which, in addition to personalized teaching based on multiplied assessment, promote learner motivation through cooperation and creativity..